Configuração acústico-articulatória das vogais orais do português brasileiro pré e pós-exercício vocal - França, Fernanda Pereira (2018)
Introduction: The production of oral vowels is an articulatory phenomenon, since changing the position of some phonoarticulatory organs directly interferes with the production of oral vowels. Little is still understood about the influence of the sound source on the organs responsible for speech production, and vice versa. There is an interest in understanding the acoustic mechanisms of speech production, especially the oral vowels / a /, / i / and / u /, which comprise the ends of the acoustic triangle. Objective: To analyze the acoustic triangle of the Brazilian vowels / a /, / i / and / u / pre and post vocal exercises. Methodology: Twelve women with vocal nodules (GE) and 12 vocally healthy (CG) participated in the study. They were submitted to the speech recording of the vehicle phrases: " I say little potato" and "I say little kite" and "I say little pupa", containing the vowels / a /, / i / and / u /. The voices were collected at the LIEV, using Fonoview software. The SG and CG were oriented to perform vocal techniques, being distributed as follows: 8 women performed the tongue vibration exercise; 10 - the exercise with high resistance straw; and 6 - the overlapping exercise. The groups were chosen at random, only 3 subjects were chosen to perform another technique that did not correspond to the tongue vibration, due to the inability. The exercises were performed for 5 minutes and every minute a new vocal recording occurred. A total of 6 vocal recordings were performed. Results: Women with vocal nodules decrease values of F0 and F1 of the vowel / u / after 5 minutes of sonicated tongue vibration exercise. They present lower values of F0 and F1 in relation to the vocally healthy women from the first minute of execution of the exercise with high resistance straw, and only F1 after 5 minutes of execution. The vowel triangle of vocally healthy women presents more noticeable and significant modifications before and after vocal exercise when compared to women with vocal nodules. Conclusion: The vocal tract size caused by the effects of semi-fluid vocal tract exercises (tongue vibration and high resistance straw) does not significantly interfere in the distinctiveness of all vowels. The performance of the semi-fluid vocal tract exercise, especially the high resistance straw, causes oropharynx to expand of women with nodules compared to vocally healthy women.